Third-generation antivenomics analysis of the preclinical efficacy of Bothrofav® antivenom towards Bothrops lanceolatus venom - Pla Ferrer, Davinia (2019)
Bothrops lanceolatus inflicts severe envenomings in the Lesser Caribbean island of Martinique. Bothrofav®, a monospecific antivenom against B. lanceolatus venom, has proven highly effective at the preclinical and clinical levels. Here, we report a detailed third-generation antivenomics quantitative analysis of Bothrofav®. With the exception of poorly-immunogenic peptides, Bothrofav® immunocaptured all the major protein components. These results, along with previous preclinical and clinical observations, underscore the high neutralizing efficacy of the antivenom against B. lanceolatus venom.